Effect of Andaliman (Zanthoxylum acanthopodium DC) Extracts upon Permeability and Hidrophobicity of Bacillus cereus - Adolf JN Parhusip; Betty Sri Laksmi Jenie; Winiati Pudji Rahayu; Sedarnawati Yasni (Jurnal Teknologi dan Industri Pangan, 2005)
Andaliman spice is usually added as one of main spices in cooked fish and meat. Andaliman seeds were extracted using maceration method with nonpolar, semipolar and polar solvents. The result showed that the three kinds of andaliman extract had antibacterial activity on Bacillus cereus, especially during exponential phase (8 hour incubation period). Ethyl-acetate extract of Andaliman showed the highest antibacterial activity toward B. cereus with MIC and MBC values being 0.2% and 0.8% respectively. The permeability of B. cereus was observed at the dose of 2.5 MIC and 60.30% hydrophobicity leakage was obtained at 6% andaliman extracted by ethyl-acetate. Key words: Andaliman, extract, hydrophobicity, antibacterial, cell- leakage.